Maternal Work Motivation, Work–Family Balance, and Family Subjective Well-Being - Istiqlaliyah Muflikhati; Octaria Intan Cahayani; Pudji Muljono; Irni Rahmayani Johan; Ismayanti Pratiwi (WISE Pendidikan Indonesia, 2026)
The participation of women, particularly mothers, in the workforce has continued to increase, bringing various challenges in balancing work demands and family responsibilities, which may affect family well-being. This study aimed to analyze the effects of maternal work motivation and work–family balance on family well-being and to examine their implications for children’s educational development. The study employed a quantitative approach with a cross-sectional design using a survey method conducted across Indonesia. Data were collected through a survey method involving families with working mothers who had preschool- and school-aged children. The respondents were mothers, and the study covered several regions in Indonesia. A total of 108 families participated in this study. Data were analyzed using descriptive statistics and Structural Equation Modeling (SEM). The results indicated that maternal work motivation, work–family balance, and family well-being were generally at a moderate level (57.4%). Economic motivation was identified as the dominant reason for mothers to engage in paid work. The SEM analysis revealed that work–family balance had a significant positive direct effect on family well-being. In addition, maternal work motivation had a positive effect (with coefficient 0.577) on both work–family balance (with coefficient 0.479) and family well-being. These findings highlight the importance of maternal work motivation and balanced role management in promoting family well-being among working-mother families. One implication of this research is that working mothers can continue to play an active role in their children's educational development while effectively maintaining a conducive learning environment at home, thereby contributing significantly to the implementation of education within the family.